Correspondence Between Cognitive and Audiological Evaluations Among the Elderly: A Preliminary Report of an Audiological Screening Model of Subjects at Risk of Cognitive Decline With Slight to Moderate Hearing Loss - Castiglione, Alessandro; Casa, Mariella; Gallo, Samanta; Sorrentino, Flavia; Dhima, Sonila; Cilia, Dalila; Lovo, Elisa; Gambin, Marta; Previato, Maela; Colombo, Simone; Caserta, Ezio; Gheller, Flavia; et al. (Frontiers in Neuroscience, 2019)
Epidemiological studies show increasing prevalence rates of cognitive decline and hearing loss with age, particularly after the age of 65 years. These conditions are reported to be associated, although conclusive evidence of causality and implications is lacking. Nevertheless, audiological and cognitive assessment among elderly people is a key target for comprehensive and multidisciplinary evaluation of the subject’s frailty status. To evaluate the use of tools for identifying older adults at risk of hearing loss and cognitive decline, and to compare skills and abilities in terms of hearing and cognitive performances between older adults and young subjects, we performed a prospective cross-sectional study, using supraliminal auditory tests. The relationship between cognitive assessment results and audiometric results was investigated and reference ranges for different ages or stages of disease determined. Patients older than 65 years (n = 146), with different degrees of hearing function, were enrolled. Each subject underwent an extensive audiological assessment including tonal and speech audiometry, Italian Matrix Sentence Test, and speech audiometry with logatomes in quiet. Cognitive function was screened and then verified by experienced clinicians using the Montreal Cognitive Assessment Score, the Geriatric Depression Scale, and further investigations in some. Forty-three subjects were excluded due to missing data or exclusion criteria; 123 were enrolled during 2016–2019 at the clinic of Otorhinolaryngology of the University Hospital of Padua, as part of the PRIHTA-IDECO 2013 project: 103 were > 65 years of age and 20 were younger participants (as controls). Cognitive functions showed correlation with the audiological results in post-lingual hearing-impaired patients, in particular with those affected by slight to moderate hearing loss and aged more than 70 years. Audiological testing can thus be useful in clinical assessment and identification of patients at risk of cognitive impairment. The study was limited by its sample size (C.I. 95%; C.L. 10%), strict dependence on language, and hearing threshold. Further investigations should be conducted to confirm the reported results and to verify similar screening models. This approach could be implemented for assessment of cochlear implants and hearing aid receivers, in individuals with severe to profound hearing loss, at different ages.